2001
DOI: 10.2739/kurumemedj.48.267
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Evaluation of Surgical Treatment for Early Gallbladder Cancer.

Abstract: We evaluated the therapeutic principles for early gallbladder cancer based on clinicopathological characteristics and outcomes in 27 patients encountered at the Kurume University Hospital between January, 1975 and December, 1999. Concerning the depth of wall penetration, 15 patients had mucosal cancers (m-cancers), and 12 patients muscularis propria cancers(mpcancers). The gross patterns were Ip (pedunculated) in 16 patients, Is (sessile) in 3 patients, Ila (flat elevated) in 4 patients, and Ilb (flat) in 4 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…The lymphatic drainage pathway has been well described by Ito et al [29] and Uesaka et al [30]. Kinoshita et al [31] reported that lymphatic and venous infiltrations were present in 33.3% of T1b gallbladder carcinomas despite the absence of lymph node metastasis and perineural infiltration [31]. Mizumoto et al [32] reported lymph node metastasis in 15.7% and lymphatic infiltration in 18.4% of T1b carcinomas.…”
Section: Discussionmentioning
confidence: 90%
“…The lymphatic drainage pathway has been well described by Ito et al [29] and Uesaka et al [30]. Kinoshita et al [31] reported that lymphatic and venous infiltrations were present in 33.3% of T1b gallbladder carcinomas despite the absence of lymph node metastasis and perineural infiltration [31]. Mizumoto et al [32] reported lymph node metastasis in 15.7% and lymphatic infiltration in 18.4% of T1b carcinomas.…”
Section: Discussionmentioning
confidence: 90%
“…A rational approach that recommends wedge resection of the liver involving the gallbladder bed as well as a regional lymph node dissection of the hepatoduodenal ligament was proposed in 1954 [36], and regional lymph node dissection was recommended in 1963 [37]. Lymphatic and venous infiltrations were reported to be present in 33.3% of T1b cancers [38], and lymph node metastasis and lymphatic infiltration was shown in 15.7 and 18.4% of T1b cancers, respectively [39]. Another study found no lymph node metastasis or lymphatic or perineural infiltration in the T1a tumors [40].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of this form of gallbladder cancer is excellent with a cholecystectomy [2,11,14,16,18] and radical cholecystectomy. The 5 year survival fluctuates between 70% and 100% [2,7,8,11,14,[16][17][18][19][20][21]26]. In our experience, we encountered one death (radical cholecystectomy) not related to the surgery (myocardial infarction).…”
Section: Discussionmentioning
confidence: 91%
“…For others, the cholecystectomy is sufficient only for the pT1a form (mucosal tumor). A radical resection (cholecystectomy associated with hepatectomy and lymphadenectomy) is indicated for the pT1b form (involvement of the muscularis layer) [20][21][22]. This controversy seems to found its explanation in the fact that these authors find a node extension in the PT1b form [14,20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation